RENAL FUNCTION TEST ON THE BASIS OF SERUM CREATININE AND UREA IN TYPE-2 DIABETICS AND NONDIABETICS - Singh, P.; Khan, S.; Mittal, and R. K. (BALI MEDICAL JOURNAL; Vol 3 No 1 (2014), 2014)
Background: Type-2 diabetes mellitus has quickly become a global health problem due to rapidly increasing population growth, aging, urbanization and increasing prevalence of obesity and physical inactivity. Diabetic nephropathy is one of the major causes of chronic renal failure. Both serum urea and creatinine are widely used to assess the function of kidney. This study was conducted to observe the impaired renal function in type 2 diabetics and compare with non-diabetics controls. Method: To determine the incidence of renal dysfunction in diabetics in Nepalgunj medical college and Hospital , Nepalgunj , Banke, Nepal , blood samples from 100 diabetic subjects and 100 non-diabetic controls were taken between the period 1 st February  , 2012  to  31 st January , 2013 for investigation of  plasma glucose fasting(FPG), blood urea and serum creatinine. These biochemical parameters were determined by using a fully automated clinical chemistry analyzer. Results : Our findings showed that the level of blood urea (P<0.0001, 95%Cl) and serum creatinine (P?0.0004,95%Cl ) were significantly higher in type 2 diabetics as compared to non-diabetics in both male and female. There was no significant difference between diabetic male and female. 15 out of 100 diabetes samples have high urea level whereas 7 out of 100 had increased creatinine level. In control only 3 samples had high urea value and 1 had high creatinine level. There was statistical signi?cant increased in urea level with increased in blood sugar level. Conclusion: Blood urea and creatinine is widely accepted to assess the renal functions. Good control of blood glucose level is absolute requirement to prevent progressive renal impairment.
Keywords: Type 2 diabetes mellitus, urea, creatinine , renal function